Ammonium enrichment reduces the diversity and changes the composition of ammonia-oxidizing microbial communities in agricultural soil media - SHERLY ASNATH SAUKOLY; VINCENTIA IRENE MEITINIARTI; RULLY ADI NUGROHO; AGNA SULIS KRAVE (Society for Indonesian Biodiversity, 2024)
Abstract. Saukoly SA, Meitiniarti VI, Nugroho RA, Krave AS. 2024. Ammonium enrichment reduces the diversity and changes the composition of ammonia-oxidizing microbial communities in agricultural soil media. Biodiversitas 25: 916-923. Nitrification is the process of ammonium oxidation to form nitrites and nitrates. Ammonium availability in the soil is one of the factors influencing the activity, abundance, and diversity of ammonia-oxidizing microorganisms (AOM). This study aimed to determine the effect of enriching a soil media with different ammonium concentrations on the abundance and diversity of AOM as well as the potential for nitrification. Soil as the media was prepared from an agricultural land receiving cow dung sewage. The media was then placed in the microcosms, and was added to a nitrification medium containing ammonium at three levels; 0 (control soil), 200 (low ammonium-enriched soil), and 500 mg L-1 (high ammonium-enriched soil). The microcosms were further incubated for 42 days at room temperature. The nitrification potential determination was based on the formation of nitrite from ammonium oxidation. The abundance of AOM and the potential nitrification were measured every 14-day interval, including day 0 as the initial condition. The AOM composition was analyzed based on the similarity level of the amoA gene sequence to the NCBI BLAST GenBank database. However, this analysis was only conducted for the control and high ammonium-enriched soil. This study indicated that ammonium enrichment increased the nitrification activity and the abundance of AOM, but it decreased the diversity of AOM communities. There were positive correlations between nitrification and nitrate potential, as well as between ammonium content and AOM abundance. Negative correlations appeared between pH and nitrification potential, nitrate concentrations, ammonium concentrations, and MPN. The diversity of ammonium-oxidizing archaea (AOA) in the control soil was higher than in the high ammonium-enriched soil. The enrichment with ammonium also changed the AOA composition. The Candidatus Nitrosocosmicus oleophilus strain of the MY3 chromosome was the most dominant archaea in the control and high ammonium-enriched soil. This implies that the high diversity of AOA in this soil may be beneficial for further use of the soil as a source for inocula in the development of nitrifiers-based biofertilizers.